2004
DOI: 10.1523/jneurosci.3340-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Autism and Abnormal Development of Brain Connectivity: Figure 1.

Abstract: It has been said that people with autism suffer from a lack of "central coherence," the cognitive ability to bind together a jumble of separate features into a single, coherent object or concept (Frith, 1989). Ironically, the same can be said of the field of autism research, which all too often seems a fragmented tapestry stitched from differing analytical threads and theoretical patterns. Defined and diagnosed by purely behavioral criteria, autism was first described and investigated using the tools of behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
804
6
23

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,085 publications
(901 citation statements)
references
References 69 publications
68
804
6
23
Order By: Relevance
“…For example, parietal cortex in subjects with autism exhibits a ~ 50% reduction in protein levels of the enzymes that synthesize GABA, glutamic acid decarboxylase (GAD) 65 and 67 (Fatemi et al, 2002). Both of these observations appear to be fully consistent with the frequently reported hypersensitivity (Cascio et al, 2007;Blakemore et al, 2006) and abnormally widespread (Belmonte et al, 2004) cerebral cortical response to skin stimulation in autism. If parietal cortical pericolumnar lateral inhibitory interactions are, in fact, deficient in subjects with autism, and if adaptation-induced spatial funneling of the primary somatosensory cortical response to repetitive skin stimulation is achieved via GABA-mediated postsynaptic inhibitory mechanisms intrinsic to primary somatosensory cortex, subjects with autism should not be expected to exhibit the adaptation-induced improvement of tactile spatial localization capacity that occurs reliably in neurologically normal subjects.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, parietal cortex in subjects with autism exhibits a ~ 50% reduction in protein levels of the enzymes that synthesize GABA, glutamic acid decarboxylase (GAD) 65 and 67 (Fatemi et al, 2002). Both of these observations appear to be fully consistent with the frequently reported hypersensitivity (Cascio et al, 2007;Blakemore et al, 2006) and abnormally widespread (Belmonte et al, 2004) cerebral cortical response to skin stimulation in autism. If parietal cortical pericolumnar lateral inhibitory interactions are, in fact, deficient in subjects with autism, and if adaptation-induced spatial funneling of the primary somatosensory cortical response to repetitive skin stimulation is achieved via GABA-mediated postsynaptic inhibitory mechanisms intrinsic to primary somatosensory cortex, subjects with autism should not be expected to exhibit the adaptation-induced improvement of tactile spatial localization capacity that occurs reliably in neurologically normal subjects.…”
Section: Introductionmentioning
confidence: 64%
“…For example, some subjects with autism exhibit hyperarousal to natural sensory input, and a decreased ability to select among competing sensory inputs ( . Although many reports acknowledge a widespread neocortical dysfunction in autism, it is less widely recognized that the dysfunction is non-uniform -e.g., the excessive responsivity of primary sensory cortex to peripheral stimulation is accompanied (in the same subject) by abnormally low activation/responsivity in cortical regions devoted to higher-order information processing (Belmonte et Consideration of the above-described observations, together with the relatively recent demonstration that autism is associated with mutation in regions centered around the GABA A -β3 receptor subunit gene, led some researchers (Belmonte et al, 2004;Polleux and Lauder, 2004) to suggest that the neocortical dysfunction in this disorder may be attributable to a deficiency during early development in GABA-mediated synaptic neurotransmission. According to this view, the excessive excitatory neurotransmission within low-order neocortical processing areas that accompanies insufficient GABA-mediated neocortical inhibition leads to the experience-driven abnormalities in neocortical functional connectivity characteristic of autism.…”
Section: Discussionmentioning
confidence: 99%
“…47 These results are consistent with the local deregulation of networks involved in working memory and attention, with a possible increase in local connectivity and a selective loss of long-range connectivity. 48 Different expression patterns for human SLC25A12 and its mouse ortholog We found that SLC25A12 was expressed mostly in the brain during human embryonic and fetal development. However, this restricted pattern of expression changes after birth, as high levels of SLC25A12 expression have been reported in skeletal muscle, heart, pancreas and kidney in adults, with low levels of expression observed in the brain.…”
Section: Discussionmentioning
confidence: 90%
“…Autism is neurodevelopmental in nature, and atypical development of neural connectivity has been suggested to underlie its key phenotypic features [125]. A set of genes involved in neurodevelopmental processes that mediate the formation, stabilization, and pruning of synapses has been consistently associated with autism-related phenotypes in animal models [126][127][128].…”
Section: Suggested Roles Of the Ecb System In Autismmentioning
confidence: 99%